Ultrasonography in Acupuncture-Uses in Education and Research - Mabel Qi He Leow; Shu Li Cui; Mohammad Taufik Bin Mohamed Shah; Taige Cao; Shian Chao Tay; Peter Kay Chai Tay; Chin Chin Ooi (Medical Association of Pharmacopuncture Institute, 2017)
This study aims to explore the potential use of ultrasound in locating the second posterior sacral foramen acupuncture point, quantifying depth of insertion and describing surrounding anatomical structures. We performed acupuncture needle insertion on a study team member. There were four steps in our experiment. First, the acupuncturist located the acupuncture point by palpation. Second, we used an ultrasound machine to visualize the structures surrounding the location of the acupuncture point and measure the depth required for needle insertion. Third, the acupuncturist inserted the acupuncture needle into the acupuncture point at an angle of 30°. Fourth, we performed another ultrasound scan to ensure that the needle was in the desired location. Results suggested that ultrasound could be used to locate the acupuncture point and estimate the depth of needle insertion. The needle was inserted to a depth of 4.0 cm to reach the surface of the sacral foramen. Based on Pythagoras theorem, taking a needle insertion angle of 30° and a needle insertion depth of 4.0 cm, the estimated perpendicular depth is 1.8 cm. An ultrasound scan corroborated the depth of 1.85 cm. The use of an ultrasound-guided technique for needle insertion in acupuncture practice could help standardize the treatment. Clinicians and students would be able to visualize and measure the depth of the sacral foramen acupuncture point, to guide the depth of needle insertion. This methodological guide could also be used to create a standard treatment protocol for research. A similar mathematical guide could also be created for other acupuncture points in future.